High‐frequency ferromagnetic resonance of Co nanowire arrays. Issue 8 (26th March 2014) - Yuan, Lixin; Yue, Zhenxing; Meng, Siqin; Li, Longtu
<x xml:space="preserve">Abstract</x> Highly ordered arrays of Co nanowires with different diameters have been fabricated by electrodeposition in nanoporous anodic aluminum oxide membranes. The prepared Co nanowires have hexagonal close‐packed structure and are [002] preferred oriented crystalline with the c‐axis parallel to the long axis of the nanowires. The high anisotropy of Co nanowires offers the possibility to control their magnetic properties and microwave properties, which are experimentally characterized by a vibrating sample magnetometer and frequency‐swept ferromagnetic resonant flip‐chip based techniques, respectively. The nanowire arrays exhibit strong magnetic anisotropies. As for the ferromagnetic resonance frequency, it increases with increasing value of the applied field, and zero‐field ferromagnetic resonance frequencies up to 28–34 GHz. Also, the magnetic anisotropies and high ferromagnetic resonance frequency of Co nanowire arrays, are shown to be determined by the combined effect of shape anisotropy, crystalline anisotropy, and dipolar interactions between the nanowires.